2018
DOI: 10.3906/sag-1707-3
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation in uropathogenic Escherichia coli: association with adhesion factor genes

Abstract: Background/aim: Biofilm formation is a major determinant factor in the development of urinary tract infections (UTIs) by uropathogenic Escherichia coli (UPEC). Several adhesion factors are involved in attachment of bacterial cells to the urinary tract and biofilm development. Materials and methods: The possible relationship between different adhesion factor genes (AFGs) and biofilm formation among UPEC isolates was investigated. Prevalence of different AFGs including fimA, fimH, papAH, papC, papEF, sfa-S, foc/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 14 publications
5
32
0
1
Order By: Relevance
“…A study by Manuela et al reported that bio lm production was signi cantly associated with uoroquinolone resistance (30). In another similar study by Zamani et al it was found out that bio lm-producing UPEC were signi cantly associated with Fim gene (31).…”
Section: Discussionmentioning
confidence: 87%
“…A study by Manuela et al reported that bio lm production was signi cantly associated with uoroquinolone resistance (30). In another similar study by Zamani et al it was found out that bio lm-producing UPEC were signi cantly associated with Fim gene (31).…”
Section: Discussionmentioning
confidence: 87%
“…These genes encoding for the type I pili, P ( pap ), F1C ( focA ), and S-fimbriae ( sfaS ) are considered to be important virulence factors for the induction of UTI and formation of biofilm [ 53 , 54 , 55 , 56 ]. A higher prevalence of sfaS (S-fimbriae) gene was observed for UPEC strains producing moderate to strong biofilms [ 57 ]. Similarly, Adamus-Bialek et al [ 55 ] and Naves et al [ 58 ] demonstrated that the virulence genes sfa , foc , and papG were more common in strong biofilm-producing E. coli isolates.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli can adhere to different surfaces, so they can easily form biofilms, which is an important feature of their virulence [28]. Different adhesion factors produced by E. coli may promote their adhesion and biofilm development, especially phenotypic expression of type 1 fimbriae, which was shown to be related to their biofilm formation ability [29]. Pseudomonas aeruginosa, a versatile organism that can adapt to a variety of environments, not only grows in aqueous environment but also can colonize and induce opportunistic infections [30].…”
Section: Discussionmentioning
confidence: 99%